Law and Politics: Study of the Presidential Threshold in the 2019 General Election of Indonesia - JM Muslimin; Ahmad Fadoliy; Wildan Munawar (Politicon : Jurnal Ilmu Politik, 2021)
This study is intended to indicate that Indonesia's electoral system always experiences rapid dynamics in policy development. This study uses empirical normative legal research or a legal research method that uses a set of regulation relating to general elections and the rules of making positive law as reference of norms. Empirical research is also used to observe the results of human behavior in the form of physical archives. The methods are combined with the historical approach: an approach that is carried out by analyzing the debate arguments that occurred in the special committee meeting (Panitia Khusus) of the Election Draft Bill. The result of this research is the decision of the presidential threshold of 20% in the holding of presidential elections of 2019 contains the orthodox legal substance. This is because politically the law of its formation (Law No. 7 of 2017) is full of practical political interests of the ruling parties. Parties consisting of 6 factions gave a dominant opinion which leaned towards the 25% -30% threshold suggested by the government, while the other 4 factions do not agree with the high nomination threshold, because the concept of election must provide free space for each party to nominate their respective presidential candidates. The government had its own agenda to continue and extend the existing incumbent president and prevent the possibility for others. Therefore, in order to protect the agenda, high nomination threshold was proposed. Through content analyses of the regulation it can be stated that the high threshold has logical consequences for holding elections which create an insubstantial election environment and make the political climate in Indonesia unbalanced.